Client best practice guide - Kershaw, Sue; Hutchison, David (Thomas Telford, 2009)
Produced in cooperation with leading construction clients and consultants, this book offers definitive guidance to clients on the ways in which they can positively influence the success of projects during the planning, development and implementation stages, as well as during operation and final decommissioning.